2017
DOI: 10.1111/rsp3.12086
|View full text |Cite
|
Sign up to set email alerts
|

State spending for higher education: Does it improve economic performance?

Abstract: Abstract. Increases in regional spending for higher education are conventionally believed to cause increases in economic performance. However, while some empirical evidence directly or indirectly confirms this belief, some research also brings it into question and even contradicts it. This research uses panel Granger causal models to consider not only the conventional belief but also the opposite possibility -that increases in economic performance cause increases in US state spending for higher education. It e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…The results indicate that investment in human and non-human capital is responsible for an overwhelming proportion of American economic growth in the period studied (Jorgenson and Fraumeni, 1992). (Bowen and Qian, 2017) expanded the investigative range of human capital in the U.S. when they set out to study the impact of investment in higher education in the U.S. states. The results indicated that state spending on higher education does not promote an increase in economic activity, but an improvement in economic performance causes spending on higher education to increase, so it is concluded that higher education is a normal good (Bowen and Qian, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicate that investment in human and non-human capital is responsible for an overwhelming proportion of American economic growth in the period studied (Jorgenson and Fraumeni, 1992). (Bowen and Qian, 2017) expanded the investigative range of human capital in the U.S. when they set out to study the impact of investment in higher education in the U.S. states. The results indicated that state spending on higher education does not promote an increase in economic activity, but an improvement in economic performance causes spending on higher education to increase, so it is concluded that higher education is a normal good (Bowen and Qian, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It could happen because many other policy domains are outside of education, such as law enforcement, environmental infrastructure development, and others (Flink and Luis, 2016). In addition, the New York Times also reported that the limited government support for education was caused by the increased business competition and economic development policies found in several Municipalities and states in the United (Bowen and Qian 2017). Similarly, the State of Canada also revealed that the increase in the number of student enrollments in the country is inversely proportional to the allocation of education budget policies which have shrunk from 84% to 57% in the last few decades.…”
Section: Challenges Of Education Budget Policy Imple-mentationmentioning
confidence: 99%
“…Some research (Goetz & Rupasingha, 2003) shows that investing in higher education induces the brain drain effect. An important distinction between investing in higher education and the quality of human capital was provided by Bowen and Qian (2017). The authors found a relation in which economic growth precedes investment in higher education.…”
Section: Variables and Datamentioning
confidence: 99%